Can I go back to work? A case of persistent SARS-CoV-2 with advanced untreated HIV infection. (February 2022) - Wenlock, Rhys D; Brown, Colin S; Iwuji, Collins; Vera, Jaime H
We describe the case of a 30-year-old care home employee diagnosed with COVID-19 and acute untreated HIV-1. He was unable to return to work for 119 days due to concerns over transmission risk as his SARS-CoV-2 PCR remained detectable. This highlights the uncertainty in interpreting SARS-CoV-2 PCR results post-infection in acute untreated HIV.